CONSUMPTIVE LIFESTYLE BEHAVIOUR OF ADOLESCENT IN INDONESIA IN INDUSTRIAL REVOLUTION 4.0 - Firman Mansir; Amalia Undip Putri (Jurusan Sosiologi FISIP UNIB, 2021)
This research explains that adolescents are a social commodity with consumptive behaviour that has affected all circles of society. The problem is that adolescents tend to always to want have and buy expensive items. This research aimed to determine the consumptive lifestyle behaviour of adolescents in the industry 4.0 in use the development of technology and information. The method used was in the form of qualitative research. With the type of literature study with the researcher as the main instrument, it was strengthened by the instrument of documentation about literature regarding consumptive adolescents. The results showed that the consumptive behaviour of adolescents in the industry 4.0 can be seen that they buy goods that is not to fulfill their needs but to fulfill their desires. Thus, what they are excessive and it leads to extravagant, and excessive nature. Keywords : Industrial Revolution 4.0, Lifestyle ,Youth Behaviour